Early retirement in West Germany: A hazard rate model in discrete time - Sikandar Siddiqui (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1994)
In this paper, I describe a structural model of retirement behaviour, in which the multiplicityof alternative retirement ages, the possibility of unobserved heterogeneity and the absorbing state property of the retirement decision are accounted for. As it is based on a relatively simple utility maximization framework, the computational burden of the model's empirical implementation is only moderate although the sequential nature of the retirement decision is adequately captured by it. The model is estimated on an unbalanced panel of elderly West German males. The results reveal that a person's health status plays a key role in determining the timing of retirement, and that the relative intensity of the individual preference for leisure among public sector employees is, ceteris paribus, below average. Education, too, is shown to exert considerable influence on a person's tendency to retire early, but the relationship between an individual's educational status and the probability of early retirement appears to be rather complex.
Keywords: 330; Flexible Altersgrenze; Deutschland